GROWTHING THE ROLE OF FINANCES IN DEVELOPMENT OF LABOR POTENTIAL OF UKRAINE - KRUPKA, Myhaylo; KULCHYTSKYJ, Myroslav; KOVALENKO, Oleksandra (Scientific journal «World of Finance», 2020)
Introduction. The necessity of increasing the role of finance in the economy is justified and emphasized that in the conditions of the commodity mode of production they cover all components of economy. There is no exception to the labor potential that characterizes potential employees, corporations and the economy as a whole. The situation on labor market of Ukraine has significant impact on the quantitative and qualitative parameters of the labor force, where real labor potential is increasingly lagging behind the nominal. Today, the need to find financial opportunities for realizing the existing labor potential in practice and its further growth is especially acute. Purpose. The purpose of the article is to study theoretical aspects and assess the employment potential of Ukraine based on macroeconomic indicators that reflect its quantitative composition and qualitative status. Find out the influence of finance and financial policy on the development of labor potential, which manifests itself in the budget and investment activities of financial system, employment and income levels of the population. Development proposals for improvement the financial policy in terms of financial support for development of labor potential the Ukrainian economy. Results. The conceptual approaches to the modern understanding of economic nature of labor potential are formed. An estimation of macroeconomic indicators, reflecting the state and dynamics of changes in the labor potential of Ukraine, was conducted. The factors of formation the financial policy are identified and structured, the combination of which in each case reflects the objects and subjects, the form and content of financial policy. The subjects of financial system, the form of ownership, the branches and the directions of financial activity were selected as indicators of the grouping factors formation the financial policy. Conclusions. It is concluded that the financial policy and measures for its improvement are concentrated on the issues of financial resources management, which is not enough for sustainable development of economy if in the process of financial management does not always take into account the necessity to improve the efficiency of using all other types of economic resources. Among their list, a particularly important role belongs to labor resources and their potential, the growth of which will contribute to replacing the shortage of skilled labor. Proposals to improve the financial policy in the part of formation and development of labor potential of Ukraine are developed.